Prevention of financial corruption by selecting the most suitable employee; its mechanisms in Islamic law and reviewing its applications in Libyan law - Amhimmid, Abdulbari Almabrouk Alfaytouri; Negasi, Mohamed Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2022)
The employee is considered as first dam to preserve public finance from corruption and spend it in the correct manner. Accordingly, the research aims to demonstrate the application of Libyan law to the most important mechanisms established by Islamic Sharia to choose the employee responsible for the money, and through which it is proposed to correct the conditions and controls for assuming responsibility for public money in Libya based on The foundations of Islamic Sharia, by following the deductive and inductive approach to reach the optimal controls for selecting the trusted employee on public money, it was found that Sharia established the most important personal qualities that are based on strength, honesty, honesty and sincerity, and the professional conditions represented in the efficiency and merit of the job and the general and private standards it includes The research reached important results according to the existence of the most important of these criteria as conditions in the laws related to the job in the Libyan law. The job laws are taken into consideration as a means of selection. Rather, the presence of most standards and controls is considered as conditions during the exercise of the job Its people are in the application, and the law does not set a clear penalty for not following these controls, the research recommended a legislative intervention that sets conditions for integrity, morals and experience to be set as conditions for assuming the job, not just duties, as well as including the penalty for nullity for violating it, in addition to applying priorities according to a set of points related to those Conditions for managing the money from corruption.
Keywords: financial corruption; characteristics and controls; Islamic Sharia; Libyan law